Improving the value of coffee exports in order to improve the value of exports: A case of Rwanda - Izere, Ines (Graduate School of Development Policy and Practice, 2017)
In order for Rwanda to improve the quality of life for its people, government has prioritized coffee as a key sector to spur the economy. For the past years, while coffee has been an important commodity that brought revenues to the country, its production is still low and the value is not of high quality. The purpose of this study was to assess the possibility of increasing the value of coffee in order to increase the value of exports for the country. The coffee sector is constrained by production of ordinary coffee and the exportation of low quantities of fully washed coffee, specialty and roasted coffee. In addition, some coffee plantations are old, fertilizers are not enough and the coffee farmer is paid little money. In order to increase the value of coffee to subsequently boost exports, it would be very important to increase the price paid to the farmer, finance the coffee sector, organizational capacities of farmers, efficiency of coffee washing stations, quantity of fully washed, specialty and roasted coffee as new international clients are targeted.